Chronic disease burden and human capital investment: evidence from the chagas disease campaign in Brazil - Oliveira, Priscila Natacha de (2016)
We investigate the effects of augmented life expectancy and health improvements on human capital investment, labor supply and fertility decisions. Our main motivation is the prediction of human capital theory that a longer and healthier life encourages educational investment and female labor force participation, while discouraging fertility. To assess the magnitude of these effects, we explore a national campaign against Chagas disease in Brazil as an exogenous source of adult mortality decline and improvement in health conditions. We show that, relative to non-endemic areas, previously endemic regions saw higher increases in educational investment, measured by literacy, school attendance and years of schooling, following the campaign. Additionally, we find that labor force participation increased in high prevalence areas relative to low prevalence ones. Furthermore, we estimate a substantially higher effect on female labor force participation relative to male, suggesting that longevity gains and health improvements affected women's incentives to work, encouraging women to join the labor force. We do not find significant effects on fertility decisions.